PENGGUNAAN ALAT PERAGA BLOK PECAHAN UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PECAHAN PADA PESERTA DIDIK KELAS III SD - Amanda Niagara; Reviandari Widyatiningtyas; Deasy Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research is motivated by the low ability to understand the concept of fractions in third grade students in learning mathematics in elementary schools. The objectives of this study are (1) to find out the use of fractional block propsfor class III students (2) to determine the improvement of the ability to understand fractions concepts using fractional block propsin class III students. This research method is a quantitative research method with a research design using a pre experimental design (non design) in the form of one group pretest-posttest. This research was conducted at SDN Jati 03, Baleendah District, Bandung Regency, with a population of 62 students and a sample of 35 students. Data collection techniques used observation and tests in the implementation of learning the ability to understand the concept of fractions by using fractional block props. The results showed that (1) the use of fractional block propsin class III can help students be more active in learning and can help the ability to understand fractions concepts so that the ability to understand fractions concepts increases after being given treatment with the use of fractional block props. (2) There is an increase in the ability to understand the concept of fractions in third grade elementary school students after the use of fractional block props can be seen from the results of the average pre-test and post-test in the experimental class, namely 65.74 and 84.80